Autocratización a fuego lento: el caso de Nicaragua (2000-2024) - Macià Serra; Daniel Rodríguez Suárez; Salvador Martí i Puig (Colombia Internacional)
Objective/context: This article dissects the process of democratic regression that has taken place in Nicaragua from 2000 to the present day (2024), drawing primarily on the analytical framework developed by Javier Corrales in his 2022 work, Rising Authoritarianism. Methodology: The quarter-century period is divided into four stages. The first, from 2000 to 2006, during which a liberal democratic regime begins to shift due to spurious political interests; the second, from 2006 to 2011, when the system acquires elements of a hybrid regime and authoritarian elections are introduced; the third, from 2011 to 2019, when the modus operandi—based on co-opting the country’s most influential economic and social actors—abruptly and improvised shifts (following protests) to influence a highly repressive authoritarian system; and a fourth period in which the government deploys a legal framework aimed at curtailing and repressing any form of dissent, hollowing out all state institutions and establishing a closed authoritarian regime. Conclusions: The study concludes that this case represents a paradigmatic example of gradual democratic backsliding, in which state capture and the use of “authoritarian legalism” have been key to maintaining power. Originality: It presents an innovative approach to categorizing and classifying the variations of democratic regression processes by examining the specificities and particularities of the Nicaraguan case.